Histone Methylation Inhibitor DZNep Ameliorated the Renal Ischemia-Reperfusion Injury via Inhibiting TIM-1 Mediated T Cell Activation - Li, Jiawei; Qiu, Yue; Li, Long; Wang, Jiyan; Cheuk, Yin Celeste; Sang, Ruirui; Jia, Yichen; Wang, Jina; Zhang, Yi; Rong, Ruiming (Frontiers in Medicine, 2020)
Renal ischemia-reperfusion injury (IRI) after renal transplantation often leads to function loss of kidney grafts. However, there still lacks an efficient regimen to prevent or alleviate renal IRI. Our study focused on the renoprotection effect of 3-Deazaneplanocin A (DZNep), which was a histone methylation inhibitor. We found that DZNep significantly alleviate the renal IRI by suppressing nuclear factor kappa-B (NF-κB) and thus inhibiting the expression of inflammatory factors in renal tubular epithelial cells in vivo or in vitro. And after treated with DZNep, T cell activation was impaired in spleen and kidney, correlated with downregulated expression of T-cell immunoglobulin mucin (TIM)-1 on T cells and TIM-4 on macrophages. In addition, pretreatment of DZNep seemed not sufficient to protect the kidney, while administration of DZNep from before surgery to after surgery ameliorate the IRI most significantly. Our findings suggested that DZNep could be a novel strategy for preventing renal IRI following kidney transplantation.